Was bleibt vom urheberrechtlichen Erschöpfungsgrundsatz? - Weiß, Raphael (Mohr Siebeck, 2025)
Digitization has led to a drastic deterioration in the legal position of users consuming copyright-protected content. Raphael Weiß analyzes the legal challenges and presents innovative approaches to strengthen consumer rights under the Digital Content Directive and enable the resale of digital media in the light of copyright restrictions.
PublicationDate: 20250415
Keywords: Digital Only -- Verbreitungsrecht -- Digitale Inhalte Richtlinie -- Verbrauchererwartung -- Nutzungsrechte -- diskrepante Informiertheit -- Tiergesundheitsrecht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Europarecht